2010
DOI: 10.1631/jzus.b0900254
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a bee venom phospholipase A2 from Apis cerana cerana in the baculovirus-insect cell

Abstract: Abstract:Bee venom phospholipase A 2 (BvPLA 2 ) is a lipolytic enzyme that catalyzes the hydrolysis of the sn-2 acyl bond of glycerophospholipids to liberate free fatty acids and lysophospholipids. In this work, a new BvPLA 2 (AccPLA 2 ) gene from the Chinese honeybee (Apis cerana cerana) venom glands was inserted into bacmid to construct a recombinant transfer vector. Tn-5B-4 (Tn) cells were transfected with the recombinant bacmid DNA for expression. Sodium dodecylsulfate-polyacrylamide gel electrophoresis (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Recently, many studies have reported the therapeutic effects of melittin against cancers, neurodegenerative diseases and chronic inflammatory diseases including rheumatism (Park et al, 2004; Yang et al, 2011; Rady et al, 2017). It has been suggested that the biological activity of bvPLA 2 can be enhanced by melittin (Mingarro et al, 1995; Shen et al, 2010). Certainly, more detailed sets of experimental investigations are needed to verify its potential usefulness in the future applications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have reported the therapeutic effects of melittin against cancers, neurodegenerative diseases and chronic inflammatory diseases including rheumatism (Park et al, 2004; Yang et al, 2011; Rady et al, 2017). It has been suggested that the biological activity of bvPLA 2 can be enhanced by melittin (Mingarro et al, 1995; Shen et al, 2010). Certainly, more detailed sets of experimental investigations are needed to verify its potential usefulness in the future applications.…”
Section: Discussionmentioning
confidence: 99%
“…The primary sequence contains eight cysteine residues involved in the formation of four disulfide bonds and one N-glycosylated residue (Asn13) (Hoffman, 2006;Shipolini et al, 1974). Unlike snake PLA2 from elapid (Class IA) and viper (Class IIA/IIB) venoms, Api m 1 belongs to Group III of bee/lizard/scorpion, secretory and Ca 2þ -dependent venom PLA2s (Hoffman, 2006;Shen et al, 2010). The enzyme hydrolyzes the sn-2 ester linkage of glycerophospholipids releasing free fatty acids and lysophospholipids (Dennis et al, 2011), as illustrated in Fig.…”
Section: Phospholipase A2mentioning
confidence: 99%
“…87% and greatly impaired parasite transmission to naive mice (Moreira et al, 2002). There is great industrial and pharmaceutical interest in phospholipases due to their association with many human disorders so that the recent production of recombinant bee PLA 2 in an insect cell line is significant (Shen et al, 2010). Similarly, hyaluronidases have many uses in medicine including helping the spread of drugs in tissues and as anti-cancer agents, so that the production of a recombinant honey bee hyaluronidase may provide a new drug with great commercial potential (Reitinger et al, 2008).…”
Section: Phospholipases and Hyaluronidasementioning
confidence: 99%